2019
DOI: 10.1088/1741-4326/ab0bd4
|View full text |Cite
|
Sign up to set email alerts
|

Localized modulation of turbulence by m/n  =  1/1 magnetic islands in the HL-2A tokamak

Abstract: Modulation of turbulent electron temperature fluctuations () and density fluctuations () by an m/n  =  1/1 tearing mode island was observed in the core plasma region of the HL-2A tokamak. High spatiotemporal resolution two-dimensional images of show the first evidence that the turbulence modulation occurs only when the island width exceeds a certain threshold value ( cm) and the modulation is localized merely in the inner area of the island due to significant alteration of local profiles and turbulence drives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 43 publications
(59 reference statements)
12
34
0
Order By: Relevance
“…Possible concomitant transient changes in T e can there-fore be studied across growing islands in non-equilibrium conditions, in contrast to saturated islands. T e modifications by saturated islands has been reported earlier 29,30 .…”
Section: Experimental Overviewsupporting
confidence: 56%
“…Possible concomitant transient changes in T e can there-fore be studied across growing islands in non-equilibrium conditions, in contrast to saturated islands. T e modifications by saturated islands has been reported earlier 29,30 .…”
Section: Experimental Overviewsupporting
confidence: 56%
“…In other words, this turbulence outside an MI can spread into the MI if its amplitude is sufficiently large 30 . In the recent DIII-D 31 and HL-2A 32 experiments 12 , 33 , 34 , observations which seem to result from the spreading of the density and temperature turbulence towards the O-point of an MI are reported. In addition, the nonlinear electrostatic gyrokinetic simulation based on the KSTAR plasma equilibrium and profiles showed that turbulence and the heat can spread into an MI which was initially stable region 35 .…”
Section: Resultsmentioning
confidence: 97%
“…This implies that the turbulent transport around an MI can be also modified, meaning that the evolution of plasma turbulence and the evolution of the MI are coupled. However, there has been relatively little experimental research progress 7 , 9 , 11 , 12 in addressing the effects of plasma turbulence on the MI evolution to date.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the interaction between an island and turbulence has been extensively studied [25,26]. Their interactions are known to result in coupled evolution between an island and turbulence [27,28,29,30,24]. Turbulence can be modified by the island associated change of the background pressure [31,32] and flow [33,34,35,36,37,38] profiles [39], which in turn affects the evolution of the island [27,28,29,30,24].…”
Section: Resultsmentioning
confidence: 99%
“…Their interactions are known to result in coupled evolution between an island and turbulence [27,28,29,30,24]. Turbulence can be modified by the island associated change of the background pressure [31,32] and flow [33,34,35,36,37,38] profiles [39], which in turn affects the evolution of the island [27,28,29,30,24]. Understanding the formation and evolution of the stochastic layer in the pedestal region should also require considering intricate turbulence effects.…”
Section: Resultsmentioning
confidence: 99%